Menulis Reflektif melalui Pembelajaran Mendalam sebagai Sarana Penguatan Karakter Siswa - Rizki Herdiani; Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2026)
21st-century education demands the development of students who are not only academically intelligent but also character- and socially mature. Reflective writing is an effective pedagogical strategy for connecting learning experiences with character development. This article systematically examines the role of reflective writing within a deep learning framework through a qualitative literature review approach. The study results indicate that reflective writing enhances students' self-awareness and integrity by encouraging introspection, evaluation of the learning process, and recognition of strengths and weaknesses. This activity also serves as a metacognitive tool, helping students organize, monitor, and evaluate their own learning strategies. Furthermore, reflective writing strengthens empathy and social awareness through engagement in collaborative projects, social experiences, and value reflection, enabling students to understand others' perspectives and foster environmental stewardship. Integrating reflection into contextual learning contexts for example, community service activities, class projects, or value discussions—facilitates the internalization of character values ​​such as responsibility, honesty, and cooperation. The effectiveness of reflective writing is even greater when it is designed as a core part of a deep learning strategy, rather than simply an additional assignment. By systematically integrating reflection, students are able to continuously connect learning experiences with moral and social values, build authentic understanding, and internalize character holistically. These findings confirm that reflective writing is not merely an academic exercise, but a crucial mechanism for developing students with self-awareness, integrity, social concern, and responsibility in real life.